Situation Report: Hungary, 19 May 1988 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Stage Is Set / by Alfred Reisch Some Preliminary Facts and Figures / by Alfred Reisch Independent Political Groups Mushroom / by Judith Pataki First Independent Hungarian Labor Union Established / by Edith Markos Bognar Speaks Out at International Economic Conference / by Karoly Okolicsanyi Nyers Tells More about Why the 1968 Reforms Were Stopped / by Karoly Okolicsanyi